SOCIAL IMPACTS OF MODERNIZATION ON THE TAPPERS: A STUDY ON AHMAD TOHARI'S BEKISAR MERAH - Suparman S.S (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
The Mimetic and interdisciplinary approach covering economy. history. culture. and ecology used in this research are mainly aimed at revealing the social impacts of modernization on the tappers as reflected in Ahmad Tohari's Bekisar Merah. The analysis shows that modernization does not only cause positive impacts but also negative one. which are even stronger. The bad impacts include monopoly. human and cultural conflict. imbalanced ecology. poverty, disharmony. violation of law, materialistic life. less religiosity. drop outs; and migration. The positive impacts include independence. adaptation, rationality and efficiency. The problems appear in the novel reflects the inner conflict of the author. Ahmad Tohari questions the ideas of the coming of the electricity' set in Karangsoga village. Modernization can only be enjoyed by the upper class of the society. It cannot meet the necessity of the traditional people. The tappers cannot enjoy the electricity even more. it causes misery and poverty.